2003
DOI: 10.1159/000070726
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Voice Quality Ratings Made by Japanese and American Listeners Using the GRBAS Scale

Abstract: The GRBAS scale is a widely used method for perceptual evaluation of voice quality. Two linguistically diverse groups of listeners (Japanese and American) rated 35 voice samples using the GRBAS scale. The ratings obtained from the two groups were compared to determine if the different linguistic background affected the use of the GRBAS scale. Results show that there are no significant differences between the Japanese and American listeners in the use of the Grade, Roughness and Breathiness scales. Ratings on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 12 publications
(9 reference statements)
5
47
1
1
Order By: Relevance
“…Apart from a good quality microphone and audio-recording device, no specialised instrumentation is required [2,6] . Perceptual evaluation is also quick, unobtrusive and comfortable for the client [2,36] . Further, although training in perceptual voice evaluation has been shown to improve the reliability of listener judgements [e.g., 7,19 ], extensive technical training and sophisticated technical knowledge and skill are not required.…”
Section: The Pros Of Auditory-perceptual Evaluation Of Disordered Voimentioning
confidence: 99%
“…Apart from a good quality microphone and audio-recording device, no specialised instrumentation is required [2,6] . Perceptual evaluation is also quick, unobtrusive and comfortable for the client [2,36] . Further, although training in perceptual voice evaluation has been shown to improve the reliability of listener judgements [e.g., 7,19 ], extensive technical training and sophisticated technical knowledge and skill are not required.…”
Section: The Pros Of Auditory-perceptual Evaluation Of Disordered Voimentioning
confidence: 99%
“…In addition, even if previous research has shown that raters of different linguistic and cultural background do not show significant differences when rating the same voice [21], it is not known whether a change of the voice samples from English to Italian impacts the reliability and validity of the CAPE-V. Finally, there are clinical implications in knowing whether the CAPE-V can discriminate among dysphonias resulting from differing underlying conditions.…”
Section: Introductionmentioning
confidence: 98%
“…In our area, there are some studies along these lines, especially on interobserver assessment with different levels of knowledge and professional experience, as well as professionals from different countries; however, the authors did not find high levels of disagreement, pointing to perceptual scale as an excellent clinical instrument 13,14 . We should consider that in view of vocal complaint and/or abnormalities in one of the assessment, the subject should be further investigated.…”
Section: Discussionmentioning
confidence: 91%